Hyperbranched polyamine dendrimer-based polyesteramide composite nanofiltration membrane and preparation method thereof
By using ethanolamine and piperazine to regulate the interfacial polymerization reaction of hyperbranched polyamine dendrimers in nanofiltration membrane preparation, the problem of irregular amino group distribution at its end is solved, the selection separation performance and structural distribution of the nanofiltration membrane are improved, and low-cost and efficient membrane preparation is achieved.
Patent Information
- Application Number
- CN202510139051.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-11
AI Technical Summary
During the preparation process of existing nanofiltration membranes, the terminal amino group distribution of hyperbranched polyamine dendrimers is irregular, affecting their reactivity and membrane performance, resulting in poor selection and separation performance, and the preparation process is complicated and costly.
Ethanolamine and piperazine are used to regulate the interfacial polymerization reaction of hyperbranched polyamine dendrimers and polyacid chloride compounds, and a composite nanofiltration membrane with dense active layer and good separation performance is selected through the interfacial polymerization reaction.
The efficient application of hyperbranched polyamine dendrimers in nanofiltration membranes is achieved, which improves the selection and separation performance and structural distribution of the membrane, simplifies the preparation process, and reduces costs.
Smart Images

Figure CN119793246A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane separation, and in particular relates to a hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane and a preparation method thereof. Background Art
[0002] Due to global climate change, growing population and rapid economic development, rigid water demand has increased. The dual pressures of water shortage and water environment deterioration have led to the development of efficient, environmentally friendly, safe and stable water treatment technologies. Membrane treatment technologies mainly include microfiltration, ultrafiltration, nanofiltration, reverse osmosis and other technologies. They have the advantages of easy operation, short design cycle, good separation effect and avoidance of secondary pollution. They are widely used in drinking water purification, wastewater treatment, seawater desalination, biochemistry and oil extraction. Among them, the separation size of nanofiltration membrane is between ultrafiltration membrane and reverse osmosis membrane, with a molecular weight cutoff of 200-1000Da, which can allow solvents, small organic molecules and some inorganic salts to pass through, and can selectively remove monovalent and polyvalent ions in water, realizing the precise separation of monovalent and divalent ions. It has broad application prospects in the field of water treatment.
[0003] Nanofiltration membranes are usually composed of a selective separation layer and a hydrophilic porous support layer prepared by interfacial polymerization of amine aqueous monomers and acyl chloride organic monomers. Their performance mainly depends on the characteristics of the selective separation layer. Therefore, exploring new reactive monomers and regulating interfacial polymerization reaction parameters to prepare nanofiltration membranes with specific selective separation performance has become a research hotspot. Dendritic molecules have a variety of functional groups, highly branched molecular structures, controllable internal cavities and good fluid mechanics. Among them, terminal amino dendritic molecules represented by polyamide-amine have regular structural distribution and sufficient amino reaction sites. The molecular structure distribution and the number of terminal amino groups can be regulated by changes in different generations, making them ideal substances for participating in interfacial polymerization reactions. Existing research has modified the terminal amino groups of polyamide-amine with carbon nanotubes, 2,3-epoxypropyltrimethylammonium chloride, 1,3-propane sultone and other molecules, and then added them to a piperazine solution for interfacial polymerization with trimesoyl chloride to prepare nanofiltration membranes for hard water softening. There are also studies that cross-link polyamide-amine with zeolite imidazolate skeletons, nanoparticles, graphene oxide, etc. to prepare nanofiltration membranes with dye separation properties. This often requires more complicated preparation processes and reaction materials, and the preparation cost is relatively high.
[0004] In addition to polyamide-amine dendrimers, hyperbranched polyamine dendrimers with irregular terminal amino group distribution also have multiple amino reaction sites and other functional groups. When the functional groups cannot react with acyl chloride monomers, the reaction sites of hyperbranched polyamine dendrimers will be unevenly distributed and affect the performance of the membrane prepared by the molecule participating in the interfacial polymerization reaction and the spatial structure distribution of the membrane, thereby limiting the application of hyperbranched polyamine dendrimers in the preparation of nanofiltration membranes. How to improve the reactivity of hyperbranched polyamine dendrimers with irregular terminal amino group distribution and improve the performance of nanofiltration membranes prepared with the participation of the molecules still needs further research. Summary of the invention
[0005] In view of this, the present invention aims to propose a hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane and a preparation method thereof, and uses ethanolamine and piperazine to regulate the interfacial polymerization reaction of hyperbranched polyamine dendrimers and polyacyl chloride compounds, thereby preparing a composite nanofiltration membrane with a dense active layer and good selective separation performance.
[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] A hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane, the hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane is composed of a separation layer and a porous support layer, the separation layer is prepared by interfacial polymerization of an aqueous phase monomer solution and an organic phase monomer solution;
[0008] The aqueous phase monomer is a compound of hyperbranched polyamine dendrimer and ethanolamine, or a compound of hyperbranched polyamine dendrimer, ethanolamine and piperazine, and the organic phase monomer is a polyacid chloride compound.
[0009] Furthermore, the hyperbranched polyamine dendrimer is a dendritic coating curing agent CYD-D014.
[0010] Furthermore, the polyacyl chloride compound is at least one of trimesoyl chloride, terephthaloyl chloride and isophthaloyl chloride.
[0011] Furthermore, the porous support layer is a hydrophilic ultrafiltration membrane, the molecular retention capacity is preferably 50,000 to 100,000 Daltons, and the pure water contact angle in the atmospheric environment is 20° to 50°.
[0012] A method for preparing a hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane comprises the following steps:
[0013] S1, dissolving the hyperbranched polyamine dendrimer and ethanolamine, or the hyperbranched polyamine dendrimer, ethanolamine and piperazine together in ultrapure water, adjusting the pH to 11.3-11.6, to obtain an aqueous monomer solution; dissolving the polyacyl chloride compound in a non-polar organic solvent, to obtain an organic monomer solution;
[0014] S2, pouring the aqueous monomer solution onto the surface of the porous support layer to wet it, and then pouring out excess aqueous monomer solution to remove residual droplets on the surface of the porous support layer;
[0015] S3, pouring the organic phase monomer solution onto the surface of the porous support layer after the operation in S2 and infiltrating it to start an interfacial polymerization reaction, and after the interfacial polymerization reaction is completed, pouring out the excess organic phase monomer solution;
[0016] S4, washing the surface of the porous support layer after the operation in S3 with a non-polar organic solvent to terminate the interfacial polymerization reaction, and then performing heat treatment to obtain the hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane.
[0017] Furthermore, the concentration of the hyperbranched polyamine dendrimers in the aqueous monomer solution is 0.1-1 w / v%. When the concentration of the hyperbranched polyamine dendrimers is too low, fewer amino sites participate in the interfacial polymerization reaction, making it difficult to improve the efficiency of the separation layer. When the concentration of the hyperbranched polyamine dendrimers is too high, due to too many amino reaction sites, a very dense separation layer is easily formed, which reduces the permeability of the separation layer. Preferably, the concentration of the hyperbranched polyamine dendrimers in the aqueous monomer solution is 0.3 w / v%.
[0018] Furthermore, the concentration of ethanolamine in the aqueous monomer solution is 0.01-0.2 w / v%. Ethanolamine is a small molecular monomer containing one amino group and one hydroxyl group. When the concentration is too low, the regulating effect on the hyperbranched polyamine dendrimer is limited. When the concentration is too high, the diffusion of the hyperbranched polyamine dendrimer into the organic phase will be inhibited. Furthermore, in order to study the regulating effect of ethanolamine on the interfacial polymerization reaction of hyperbranched polyamine dendrimers and polyacyl chloride compounds, the concentration of ethanolamine in the aqueous solution is preferably 0.01 w / v%, 0.03 w / v%, 0.05 w / v%, 0.1 w / v%, and further preferably 0.03 w / v%.
[0019] Furthermore, the concentration of piperazine in the aqueous monomer solution is 0.01-0.1 w / v %. Piperazine has high reactivity. Too high a concentration will occupy the reaction sites of the hyperbranched polyamine dendrimers and reduce the reaction advantage of the hyperbranched polyamine dendrimers. Furthermore, the concentration of piperazine in the aqueous monomer solution is preferably 0.03 w / v %.
[0020] Furthermore, the pH of the aqueous monomer solution in S1 is adjusted to 11.3-11.6; the pH adjustment method is to add an inorganic base, and the inorganic base is at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate. The aqueous monomer is alkaline after being dissolved in ultrapure water, and the alkaline condition can promote the absorption of hydrogen chloride, a byproduct of the interfacial polymerization acylation reaction, and promote the forward movement of the reaction. Preferably, the pH of the aqueous monomer solution is 11.5.
[0021] The concentration of the polyacyl chloride compound in the organic phase monomer solution is 0.05-2 w / v%. When the concentration of the polyacyl chloride compound is too low, the interfacial polymerization reaction will be insufficient. When the concentration of the polyacyl chloride compound is too high, the polyacyl chloride compound participating in the reaction is limited due to the self-limiting property of the interfacial polymerization reaction. Preferably, the concentration of the polyacyl chloride compound is 0.1 w / v%.
[0022] Furthermore, the non-polar organic solvent in S4 is one or more of n-hexane, isoparaffin, n-heptane, and n-octane.
[0023] Further, the infiltration time of the aqueous monomer solution in S2 is 4 to 10 minutes. More preferably, it is 5 minutes. After the aqueous monomer solution is infiltrated, the excess aqueous monomer solution on the surface is poured off, and the residual liquid is removed with a rubber scraper or an air knife, so that the surface of the porous support layer reaches a "moist but not wet" state, and no obvious droplets are visible to the naked eye, so as to avoid the residual liquid from participating in the subsequent interfacial polymerization reaction.
[0024] Furthermore, the interfacial polymerization time in S3 is 30 to 60 seconds, more preferably 40 seconds; the reaction temperature is 23 to 27°C, and the relative humidity of the environment during the reaction is 30 to 50% RH. Interfacial polymerization is a self-limiting reaction. If the reaction time is too short, the interfacial polymerization reaction will be incomplete, and the reaction will not continue after the reaction is completed if the reaction time is extended; if the reaction temperature is too low, the reaction rate will be reduced, and if the reaction temperature is too high, the reaction rate will be too fast, increasing the uncontrollability of the interfacial polymerization reaction; if the environmental humidity is too low, the aqueous solution or organic solution on the surface of the porous support layer is easy to volatilize, and if the environmental humidity is too high, the hydrolysis of the polyacyl chloride compound will be promoted.
[0025] Furthermore, the heat treatment temperature in S4 is 40-60°C, and the heat treatment time is 2-5 minutes. It is further preferred that the heat treatment temperature is 50°C, and the heat treatment time is 3 minutes. Too high a heat treatment temperature or too long a heat treatment time will cause the nanofiltration membrane pores to collapse, thereby reducing the permeation separation performance.
[0026] Furthermore, the hydrophilic ultrafiltration membrane is pretreated before preparation, and the pretreatment method is first soaked in a 1 v / v% ethanol solution for 12 h, then cleaned with pure water and ultrasound, and then soaked in a 1 v / v% ethanol solution for 20 min, and then cleaned with pure water and ultrasound for 2 to 4 times.
[0027] Dendritic coating curing agent CYD-D014 is produced by Weihai Chenyuan Molecular New Materials Co., Ltd. and is an industrial-grade hyperbranched polyamine dendritic molecular monomer.
[0028] The end groups of the hyperbranched polyamine dendrimer molecules used in the present invention are irregularly distributed, mainly composed of functional groups such as amino groups and ester groups, and have multiple amino reaction sites, which can undergo interfacial polymerization reaction with polyacyl chloride molecules to generate a network structure; the piperazine molecules have high reaction activity and diffusion rate, and can undergo rapid interfacial polymerization reaction with polyacyl chloride molecules; the ethanolamine molecules are small molecular substances containing one amino group and one hydroxyl group, and have strong polarity, so it is difficult to undergo interfacial polymerization reaction with polyacyl chloride monomers in non-polar organic solvents, but can form covalent bonds with amine monomers to activate reaction activity, and regulate the interfacial polymerization reaction in which the amine monomers participate.
[0029] Compared with the prior art, the hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane and the preparation method thereof described in the present invention have the following advantages:
[0030] (1) The present invention provides a hyperbranched polyamine dendrimer-based polyesteramide composite nanofiltration membrane and a preparation method thereof. The hyperbranched polyamine dendrimer is introduced as an aqueous phase monomer, and a trace amount of ethanolamine and piperazine molecules are added as regulators for the interfacial polymerization of the hyperbranched polyamine dendrimer and the polyacyl chloride monomer. The hyperbranched polyamine dendrimer and piperazine can activate the activity of ethanolamine to enable it to participate in the interfacial polymerization reaction. At the same time, piperazine can also promote the reaction activity of the hyperbranched polyamine dendrimer and enhance the retention performance of the membrane. Ethanolamine can be connected to the hyperbranched polyamine molecule through a chemical bond to improve the structural distribution of the hyperbranched polyamine dendrimer. At the same time, due to the presence of polarity in ethanolamine, the reaction rate of piperazine can be reduced, so that the interfacial polymerization reaction of the hyperbranched polyamine dendrimer and piperazine with the polyacyl chloride monomer is more balanced. The present invention achieves the regulation of the separation layer and structural characteristics of the nanofiltration membrane through the above effects, thereby preparing a polyesteramide composite nanofiltration membrane with good selective separation characteristics.
[0031] (2) The present invention can regulate the pore size distribution and selective separation performance of the separation layer of the hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane by adjusting the concentration of the hyperbranched polyamine dendrimer, piperazine, and ethanolamine. No additional technical means are required, and the performance of the prepared membrane is diversified to adapt to different water treatment needs.
[0032] (3) The preparation method of the present invention adopts traditional interfacial polymerization, and the preparation process is simple and easy to operate. The introduced hyperbranched polyamine dendrimer monomer with irregularly distributed terminal amino groups is an industrial-grade product, and the raw material cost is low and easy to obtain, so the preparation of the composite nanofiltration membrane can be achieved at low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The scanning electron microscope morphology images of the composite nanofiltration membranes prepared in Example 2, Example 6, Comparative Example 1 and Comparative Example 3 are respectively.
[0034] Figure 2 These are infrared spectra of the composite nanofiltration membranes prepared in Example 2, Example 6, Comparative Example 1, and Comparative Example 3.
[0035] Figure 3 The pore size distribution diagram of the composite nanofiltration membranes prepared in Example 2, Example 6, Comparative Example 1, and Comparative Example 3. DETAILED DESCRIPTION
[0036] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0037] The hyperbranched polyamine dendrimer mentioned in the examples and comparative examples is a dendrimer coating curing agent CYD-D014, which is produced by Weihai Chenyuan Molecular New Materials Co., Ltd. and is an industrial-grade product.
[0038] Example 1
[0039] (1) A hydrophilic polysulfone porous ultrafiltration membrane was selected as the support layer and pretreated before preparation. The pretreatment method was first soaked in a 1 v / v% ethanol solution for 12 h, then cleaned with pure water and ultrasound, then soaked in a 1 v / v% ethanol solution for 20 min, then cleaned with pure water and ultrasound for 2 to 4 times, and soaked in deionized water for use;
[0040] (2) The laboratory temperature was controlled at 25 ± 2 °C and the ambient humidity was controlled at 40 ± 10% RH;
[0041] (3) dissolving the hyperbranched polyamine dendrimer and ethanolamine in ultrapure water to prepare an aqueous monomer solution, wherein the concentration of the hyperbranched polyamine dendrimer is 0.3 w / v % and the concentration of ethanolamine is 0.01 w / v %, and then adjusting the pH to 11.5 with 0.1 w / v % NaOH; dissolving trimesoyl chloride in n-hexane to prepare an organic monomer solution, wherein the concentration of trimesoyl chloride is 0.1 w / v %.
[0042] (4) pouring the aqueous monomer solution described in step (3) onto the surface of the polysulfone porous ultrafiltration membrane and soaking it for 5 min, then pouring off the excess aqueous monomer solution and using a rubber scraper to remove the droplets remaining on the surface of the porous support layer, so that the surface remains moist but not wet, and no obvious droplets can be seen by the naked eye;
[0043] (5) pouring the organic phase monomer solution described in step (3) onto the surface of the porous support layer and infiltrating it to start the interfacial polymerization reaction. The reaction time is 40 s. After the interfacial polymerization reaction is completed, pouring out the excess organic phase monomer solution;
[0044] (6) After step (5), the surface of the porous support layer is rinsed with n-hexane solvent for 3 to 4 times, and the obtained composite membrane is immediately placed in an oven at 50° C. for heat treatment for 3 min. After the heat treatment, the hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane can be obtained.
[0045] Example 2
[0046] The only difference between Example 2 and Example 1 is that the concentration of ethanolamine is 0.03 w / v %.
[0047] Example 3
[0048] The only difference between Example 3 and Example 1 is that the concentration of ethanolamine is 0.05 w / v %.
[0049] Example 4
[0050] The only difference between Example 4 and Example 1 is that the concentration of ethanolamine is 0.1 w / v %.
[0051] Example 5
[0052] The only difference between Example 5 and Example 1 is that the water phase monomer is replaced with a mixed water phase monomer of 0.3 w / v % hyperbranched polyamine dendrimer, 0.03 w / v % piperazine, and 0.01 w / v % ethanolamine.
[0053] Example 6
[0054] The only difference between Example 6 and Example 1 is that the water phase monomer is replaced with a mixed water phase monomer of 0.3 w / v % hyperbranched polyamine dendrimer, 0.03 w / v % piperazine, and 0.03 w / v % ethanolamine.
[0055] Example 7
[0056] The only difference between Example 7 and Example 1 is that the water phase monomer is replaced with a mixed water phase monomer of 0.3 w / v % hyperbranched polyamine dendrimer, 0.03 w / v % piperazine, and 0.05 w / v % ethanolamine.
[0057] Example 8
[0058] The only difference between Example 8 and Example 1 is that the water phase monomer is replaced with a mixed water phase monomer of 0.3 w / v % hyperbranched polyamine dendrimer, 0.03 w / v % piperazine, and 0.1 w / v % ethanolamine.
[0059] Comparative Example 1
[0060] The only difference between Comparative Example 1 and Example 1 is that the aqueous phase monomer is replaced with 0.3 w / v % of hyperbranched polyamine dendrimers.
[0061] Comparative Example 2
[0062] The only difference between Comparative Example 2 and Example 1 is that the water phase monomer is replaced with 0.3 w / v % of hyperbranched polyamine dendrimers and 0.3 w / v % of ethanolamine mixed water phase monomers.
[0063] Comparative Example 3
[0064] The only difference between Comparative Example 3 and Example 1 is that the water phase monomer is replaced with a mixed water phase monomer of 0.3 w / v % hyperbranched polyamine dendrimer and 0.03 w / v % piperazine.
[0065] Comparative Example 4
[0066] The only difference between Comparative Example 4 and Example 1 is that the aqueous phase monomer is replaced with a mixed aqueous phase monomer of 0.3 w / v % hyperbranched polyamine dendrimer, 0.03 w / v % piperazine, and 0.3 w / v % ethanolamine.
[0067] Comparative Example 5
[0068] The only difference between Comparative Example 5 and Example 1 is that the aqueous phase monomer is replaced with 0.03 w / v % piperazine.
[0069] Comparative Example 6
[0070] The only difference between Comparative Example 6 and Example 1 is that the aqueous phase monomer is replaced with a mixed aqueous phase monomer of 0.03 w / v % piperazine and 0.01 w / v % ethanolamine.
[0071] Comparative Example 7
[0072] The only difference between Comparative Example 7 and Example 1 is that the aqueous phase monomer is replaced with a mixed aqueous phase monomer of 0.03 w / v % piperazine and 0.03 w / v % ethanolamine.
[0073] Comparative Example 8
[0074] The only difference between Comparative Example 8 and Example 1 is that the aqueous phase monomer is replaced with a mixed aqueous phase monomer of 0.03 w / v % piperazine and 0.05 w / v % ethanolamine.
[0075] Comparative Example 9
[0076] The only difference between Comparative Example 9 and Example 1 is that the aqueous phase monomer is replaced with a mixed aqueous phase monomer of 0.03 w / v % piperazine and 0.1 w / v % ethanolamine.
[0077] Comparative Example 10
[0078] The only difference between Comparative Example 10 and Example 1 is that the aqueous phase monomer is replaced with a mixed aqueous phase monomer of 0.03 w / v % piperazine and 0.3 w / v % ethanolamine.
[0079] Experimental Example 1
[0080] The surface morphology of some composite nanofiltration membranes prepared in the examples and comparative examples was tested by scanning electron microscopy.
[0081] Test results such as Figure 1 As shown, a is the nanofiltration membrane prepared in Example 2, b is the nanofiltration membrane prepared in Example 6, c is the nanofiltration membrane prepared in Comparative Example 1, and d is the nanofiltration membrane prepared in Comparative Example 3. By comparison, it is found that the prepared nanofiltration membranes all form a complete and smooth separation layer covering the porous support layer.
[0082] Experimental Example 2
[0083] Fourier transform infrared spectroscopy was performed on some of the composite nanofiltration membranes prepared in the examples and comparative examples.
[0084] Test results such as Figure 2 As shown in the figure, the nanofiltration membranes prepared in the figure all have amide bonds and ester bonds, indicating the formation of a separation layer; the ester bonds of the membranes prepared in Example 2 and Example 6 are partly the ester bonds of the polyamine dendritic molecule entity, and partly the ester bonds generated by the reaction of ethanolamine, and the ester bonds of the membranes prepared in Comparative Example 1 and Comparative Example 3 are the ester bonds of the polyamine dendritic molecule entity; the hydroxyl peak intensity of the nanofiltration membranes prepared in Example 2 and Example 6 increases, because there are unreacted hydroxyl groups of ethanolamine on the membrane surface, and this molecule can improve the hydrophilicity of the membrane surface and enhance the anti-fouling performance of the membrane.
[0085] Experimental Example 3
[0086] The pore size distribution test was performed on some composite nanofiltration membranes prepared in the examples and comparative examples.
[0087] The test method is to use diethylene glycol (106 Da), triethylene glycol (150 Da) and polyethylene glycol of different molecular weights (200 Da, 300 Da, 400 Da, 600 Da, 800 Da) solutions with a solution concentration of 200 ppm to test the pore size distribution of the test samples.
[0088] The pore size distribution of the composite nanofiltration membranes prepared in Example 2, Example 6 and Comparative Example 1 and Comparative Example 3 was tested. The test results are as follows: Figure 3 As shown, the pore size of the nanofiltration membrane prepared by adding ethanolamine as a water phase monomer to the hyperbranched polyamine dendrimer or the mixed solution of the hyperbranched polyamine dendrimer and piperazine is reduced.
[0089] Experimental Example 4
[0090] The performance of the composite nanofiltration membranes prepared in the experimental examples and comparative examples was tested.
[0091] The test method is as follows: using a cross-flow filtration membrane pool device, in an environment of 25°C, pre-pressing at 6 bar pressure for 40 min, after the membrane performance is stable, adjusting the test pressure to 5 bar, the cross-flow velocity to 0.45 m / s, the prepared composite nanofiltration membrane is tested for pure water flux and salt retention performance, the feed liquid NaSO 4 MgSO 4 , CaCl 2 is 2000 ppm.
[0092] The test results are shown in Table 1.
[0093] Table 1
[0094] Serial number <![CDATA[Pure water flux L / (m 2 ·h·bar)]]> Sodium sulfate retention rate (%) Magnesium sulfate retention rate (%) Calcium chloride retention rate (%) Example 1 10.06 71.68 87.01 68.23 Example 2 8.3 87.48 90.62 69.32 Example 3 5.77 61.2 89.85 81.21 Example 4 8.1 24.11 71.67 78.55 Example 5 11.36 96.33 96.72 83.6 Example 6 7.49 96.6 97.45 76.25 Example 7 6.56 97.24 97.54 67.64 Example 8 4.91 88.59 95.01 63.96 Comparative Example 1 17.63 61.27 68.27 51.36 Comparative Example 2 176.44 8.37 4.57 5.88 Comparative Example 3 23.39 81.71 86.75 69.21 Comparative Example 4 30.26 7.22 10.61 4.97 Comparative Example 5 52.79 87.85 51.35 8.36 Comparative Example 6 24.9 97.74 85.24 10.51 Comparative Example 7 13.55 98.28 93.49 13.99 Comparative Example 8 10.25 98.92 95 16.37 Comparative Example 9 7.72 99.02 97.67 19.93 Comparative Example 10 186.44 8.38 4.42 5.76
[0095] It can be seen from Examples 1 to 8 that a composite nanofiltration membrane with specific separation performance can be prepared by compounding hyperbranched polyamine dendrimers with ethanolamine and piperazine. It can be seen from Examples 1 to 4 that the nanofiltration membrane prepared by compounding an appropriate amount of hyperbranched polyamine dendrimers with an appropriate amount of ethanolamine has good calcium and magnesium retention performance, and a nanofiltration membrane with high calcium chloride / low sodium sulfate separation characteristics can be prepared by adjusting the monomer concentration; it can be further known from Examples 5 to 8 that the nanofiltration membrane prepared by adding a trace amount of piperazine to the mixed aqueous phase of hyperbranched polyamine dendrimers and ethanolamine has a high retention rate for sodium sulfate, magnesium sulfate, and calcium chloride, indicating that piperazine can regulate the interfacial polymerization reaction of hyperbranched polyamine dendrimers and ethanolamine, and participate in the reaction while enhancing the reactivity of hyperbranched polyamine dendrimers and ethanolamine.
[0096] By comparing Examples 1, 2, 3, and 4 with Comparative Example 1, it can be seen that after adding an appropriate amount of ethanolamine to the hyperbranched polyamine dendrimer, the prepared nanofiltration membrane has a more obvious effect of improving the retention of magnesium sulfate and calcium chloride. In particular, compared with Comparative Example 1, the retention rates of sodium sulfate, magnesium sulfate, and magnesium chloride in Examples 1 and 2 are significantly improved. Combined with the infrared spectrum and pore size distribution of the composite nanofiltration membrane, it is shown that an appropriate amount of ethanolamine can participate in the interfacial polymerization reaction by mixing with the hyperbranched polyamine dendrimer and regulate the pore size distribution of the prepared nanofiltration membrane. The selective separation performance of the prepared nanofiltration membrane can be changed by regulating the concentration of ethanolamine. By comparing Examples 1, 2, 3, and 4 with Comparative Example 2, it can be seen that when 0.3 w / v ethanolamine is added to the hyperbranched polyamine dendrimer, the retention rate of sodium sulfate, magnesium sulfate, and magnesium chloride in the prepared nanofiltration membrane is significantly improved. Combined with the infrared spectrum and pore size distribution of the composite nanofiltration membrane, it is shown that an appropriate amount of ethanolamine can participate in the interfacial polymerization reaction by mixing with the hyperbranched polyamine dendrimer and regulate the pore size distribution of the prepared nanofiltration membrane. The selective separation performance of the prepared nanofiltration membrane can be changed by regulating the concentration of ethanolamine. When % ethanolamine is used as the aqueous phase monomer, a complete separation layer cannot be generated, indicating that adding a trace amount of ethanolamine to the hyperbranched polyamine dendrimer is helpful to improve the performance of the prepared nanofiltration membrane, while when excessive ethanolamine is added, it is not conducive to the preparation of a complete nanofiltration membrane.
[0097] It can be seen from Examples 5, 6, 7, 8 and Comparative Example 3 that when an appropriate amount of ethanolamine is added to the mixed aqueous phase monomer of the hyperbranched polyamine dendrimer and piperazine, the retention rates of the prepared nanofiltration membrane for sodium sulfate, magnesium sulfate and calcium chloride are improved with the addition of ethanolamine. In particular, the retention rates of sodium sulfate and magnesium sulfate in Examples 5 and 6 are maintained above 95%, and the retention rates of calcium chloride are above 70%. Combined with the pore size distribution diagram of the composite nanofiltration membrane, it can be seen that adding a trace amount of ethanolamine to the mixed aqueous phase monomer of the hyperbranched polyamine dendrimer and piperazine will make the prepared nanofiltration membrane denser, which is beneficial to improving the desalination performance of the composite nanofiltration membrane; and it can be seen from Examples 5, 6, 7, 8 and Comparative Example 4 that adding excessive ethanolamine to the mixed aqueous phase monomer of the hyperbranched polyamine dendrimer and piperazine will cause defects in the prepared nanofiltration membrane, resulting in a significant decrease in salt retention performance.
[0098] It can be seen from Examples 5, 6, 7, 8 and Comparative Example 5 that a trace amount of piperazine is not easy to form a nanofiltration membrane with good performance, and adding an appropriate amount of hyperbranched polyamine dendrimers and ethanolamine to a trace amount of piperazine can effectively improve the retention performance of the prepared nanofiltration membrane for sodium sulfate, magnesium sulfate and sodium chloride; further, Examples 5, 6, 7, 8 and Comparative Examples 6, 7, 8 and 9 are analyzed. Adding an appropriate amount of the hyperbranched polyamine dendrimer to a mixed solution of piperazine and an appropriate amount of ethanolamine at the same concentration can effectively improve the retention performance of the prepared nanofiltration membrane for calcium chloride, and the retention performance for sodium sulfate and magnesium sulfate does not change much, which shows that in the aqueous phase mixed monomer, the hyperbranched polyamine dendrimer can regulate the interfacial polymerization reaction of piperazine and ethanolamine, so that the characteristics of the prepared composite nanofiltration membrane are changed; and by analyzing Comparative Examples 4 and 10, it can be seen that when the concentration of ethanolamine in the aqueous phase monomer is 0.3 w / v%, ethanolamine and a trace amount of piperazine cannot form a complete separation layer after mixing.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane, characterized in that: The hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane is composed of a separation layer and a porous support layer, wherein the separation layer is prepared by interfacial polymerization of an aqueous monomer solution and an organic monomer solution; The aqueous phase monomer is a compound of hyperbranched polyamine dendrimer and ethanolamine, or a compound of hyperbranched polyamine dendrimer, ethanolamine and piperazine, and the organic phase monomer is a polyacid chloride compound.
2. The hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane according to claim 1, characterized in that: The hyperbranched polyamine dendrimer is a dendritic coating curing agent CYD-D014.
3. The hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane according to claim 1, characterized in that: The polybasic acid chloride compound is at least one of trimesoyl chloride, terephthaloyl chloride and isophthaloyl chloride.
4. The hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane according to claim 1, characterized in that: The porous supporting layer is a hydrophilic ultrafiltration membrane.
5. The method for preparing the hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane according to any one of claims 1 to 4, characterized in that: The steps include: S1, dissolving the hyperbranched polyamine dendrimer and ethanolamine, or the hyperbranched polyamine dendrimer, ethanolamine and piperazine together in ultrapure water, adjusting the pH to 11.3-11.6, to obtain an aqueous monomer solution; dissolving the polyacyl chloride compound in a non-polar organic solvent, to obtain an organic phase monomer solution; S2, pouring the aqueous monomer solution onto the surface of the porous support layer to wet it, and then pouring out excess aqueous monomer solution to remove residual droplets on the surface of the porous support layer; S3, pouring the organic phase monomer solution onto the surface of the porous support layer after the operation in S2 and infiltrating it to start an interfacial polymerization reaction, and after the interfacial polymerization reaction is completed, pouring out the excess organic phase monomer solution; S4, washing the surface of the porous support layer after the operation in S3 with a non-polar organic solvent to terminate the interfacial polymerization reaction, and then performing heat treatment to obtain the hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane.
6. The method for preparing the hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane according to claim 5, characterized in that: The concentration of the hyperbranched polyamine dendrimer in the aqueous monomer solution is 0.1-1 w / v%, the concentration of ethanolamine is 0.01-0.2 w / v%, and the concentration of piperazine is 0.01-0.1 w / v%; the concentration of the polyacid chloride compound in the organic monomer solution is 0.05-2 w / v%.
7. The method for preparing a hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane according to claim 5, characterized in that: The non-polar organic solvent in S4 is one or more of n-hexane, isoparaffin, n-heptane and n-octane.
8. The method for preparing a hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane according to claim 5, characterized in that: The infiltration time of the aqueous monomer solution in S2 is 4 to 10 minutes.
9. The method for preparing a hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane according to claim 5, characterized in that: In the S3, the interfacial polymerization time is 30-60 seconds, the reaction temperature is 23-27° C., and the relative humidity of the environment during the reaction is 30-50% RH.
10. The method for preparing a hyperbranched polyamine dendrimer-based polyester amide composite nanofiltration membrane according to claim 5, characterized in that: The heat treatment temperature in S4 is 40-60° C., and the heat treatment time is 2-5 minutes.
Citation Information
Patent Citations
Reverse osmosis composite film and preparation method thereof
CN105664741A
Polyamide nano-film with accurately adjustable ordered pore structure and preparation method of polyamide nano-film
CN119015897A
Resin composition containing dendritic polymer and permselective membrane
JP2001106916A